Differences in emotional regulation of Bugis student and Malay cultural background Implications for counseling and guidance services - Nur Wisma; Herman Nirwana; Afdal Afdal (Universitas Negeri Padang, 2018)
Students often exert an excessive emotional reaction to a problem, thus often acting irrationally. Therefore, students need adequate emotional regulation ability. Factors that affect emotional regulation one of them is culture. This research aimed atdescribing differences in emotional regulation between students of Bugis and Malay cultural background and the implications of counseling services. This research used quantitative method of comparative descriptive type. The sample of this research is students of Bugis and Malay background of RiauUniversityconsisting of 168 students. Purposive sampling was used as the sample technique. The instrument used was an emotional regulation questionnaire with Likert scale model. The results of students' emotional regulation reliability of 0.880. Data were analyzed using t-test technique. The results of the data analysis showed that the students' emotional regulation in terms of cultural background was clasdified into high category; there is no significant difference which means that no difference between student emotional regulation of Bugis and Malay cultural background